ANALISIS KINERJA KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA TELKOMSEL JAKARTA SELATAN - Vemmi Saptiari (2013)
Quality of service are the advantages of the service provided to the consumer first and hope that can meet the desires and needs of consumers. Consumer satisfaction is a response or the response of consumers after getting service from company Telkomsel. The purpose of this study was to determine and analyze the extent to which the correspondence between the performance quality of service to customer satisfaction at Vodacom South Jakarta. This study uses primary data collected from respondents (Telkomsel Card users). The results of the 87 respondents faculty of economics courses S1 Management, University of National Development Veteran Jakarta analysis using Importance-Performancers Analyst or interest rate analysis and the concept of customer satisfaction performance is a multi-attribute models. This technique identifies the strengths and weaknesses of market supply by using two criteria: the relative importance of attributes and customer satisfaction.